Crisis in governance : a review of Bangladesh's development, 1997 - Centre for Policy Dialogue (Bangladesh) (Dhaka, Bangladesh : University Press, 1998)
Contributed articles.
Includes bibliographical references.
Keywords: Rural poor -- Bangladesh; Bangladesh -- Economic policy; Bangladesh -- Economic conditions